Measures of Spirituality/Religiosity-Description of Concepts and Validation of Instruments - Büssing, Arndt (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Why do we need more questionnaires to measure aspects of spirituality/religiosity when we already have so many well-tried instruments in use? One answer is that research in this field is growing and that new research questions continuously do arise. Several of these new questions cannot be easily answered with the instruments designed for previous questions. The field is expanding and, consequently, the research topics. Meanwhile several multidimensional instruments were developed which cover existential, prosocial, religious and non-religious forms of spirituality, hope, peace and trust—and several more. The ‘disadvantage’ of these instruments is the fact that some are conceptually broad and often rather unspecific, but they might be suited quite well for culturally and spiritually diverse populations when the intention is to compare such diverse groups. This is the reason why more research on new instruments is needed as can be found in this Special Issue, and to stimulate a critical debate about their pros and cons.